Advanced power inverter topologies and modulation techniques for common-mode voltage elimination in electric motor drive systems - Robles, Endika; Fernandez, Markel; Andreu, Jon; Ibarra, Edorta; Ugalde, Unai (Renewable & sustainable energy reviews, 2021)
The demand for more reliable and efficient electric machines and drives is constantly growing in the renewable energy and transport electrification sectors. Such drive systems are usually fed by semiconductor switch-based inverters, which, unlike balanced pure sine-wave AC sources, produce large-amplitude, high-frequency common-mode voltage (CMV) waveforms, as a result of the application of pulse-width modulation (PWM). This can lead to a number of issues, such as high electromagnetic interference, deterioration of stator winding insulation, and leakage current flow through motor bearings, which dramatically reduce the life-cycle of machines and drives. Thus, this topic has been extensively investigated in the scientific literature, where either corrective or preventive mitigation approaches have been proposed. The former attempt to relieve the damage produced, whereas the latter tackle the problem at its root, by minimizing or eliminating the CMV produced by the inverter. This work provides a comprehensive review of the major CMV mitigation/elimination solutions, with emphasis on preventive actions, in the form of inverter topology variants and/or advanced modulation techniques. A wide picture of this subject is provided to researchers and field engineers, with valuable information and practical hints for the design and development of high-performance electric drive systems. Indeed, an in-depth analysis of the most recent literature clearly shows that best results are obtained by conveniently combining alternative topologies and modulation techniques, which, in some cases, make it possible to completely suppress the CMV component. [Display omitted] •Presence of electric machines on the global energy playground is increasing significantly.•PWM-controlled inverters produce substantial common-mode voltage (CMV).•CMV causes motor/drive malfunctions and, eventually, system breakdowns.•CMV can greatly be reduced by using advanced inverter topologies and modulation techniques.•This paper provides a comprehensive review of the many works published on this topic.